Synthesis, redox chemistry, molecular and electronic structure of some cyclopentadienylcobalt pentafulvene complexes - Wadepohl, Hubert; Paffen, Franz-Josef; Pritzkow, Hans (Journal of organometallic chemistry, 1999)
The pentafulvene complexes [(C5R5)Co(C6H4R′R′′)] 3d (R=H, R′=Me, R′′=Ph), 3f (R=H, R′=Ph, R′′=C6H4NO2-4), 3g (R=H, R′=R′′=SMe) and 9 (R=Me, R′=R′′=Ph) were prepared from the respective fulvenes and [(C5R5)Co(C2H4)2] 8a,b. Protonation of 3 occurs at the fulvene C-α to give substituted cobaltocenium cations. The crystal and molecular structures of 3g, 9 and of the protonation product [3e+H]+ (R=R′=Ph) were determined. In the neutral complexes the non-planar fulvene ligands are essentially η4-coordinated with short uncoordinated exocyclic carbon-carbon double bonds. In contrast, the protonated species exhibit η5-coordinated planar five-membered rings. Using cyclic voltammetry, the complexes 3e,f and 9 were shown to reversibly undergo one-electron oxidation and reduction reactions to give the cations [3e]+, [3f]+, [9]+ and anions [3e]−, [3f]−, [9]−. Complex 3g also forms an anion [3g]−, but oxidation is irreversible. The X-band ESR spectra of [3e]−, [3e]+ and of [9]−, [9]+ were recorded. In marked contrast to the cations, the anion radicals exhibit considerable anisotropy of the g and A tensors. d-Electron spin densities ρd=0.5 for the radical anions were derived from a detailed analysis and simulation of the ESR spectra. Using extended Hückel and Fenske-Hall MO calculations for the model complex [(C5H5)Co(C5H4CH2)] 3h, the ESR and electrochemical properties were explained by the different metal participation in the HOMO (=SOMO of the cation radicals) and LUMO (=SOMO of the anion radicals).